2013
DOI: 10.1007/s13730-013-0088-8
|View full text |Cite
|
Sign up to set email alerts
|

Renal cell carcinoma presenting as AA amyloidosis: a case report and review of the literature

Abstract: A 47-year-old Caucasian man developed mild diarrhoea associated with more than 10 kg weight loss, severe fatigue and anaemia. Endoscopy demonstrated deposits of AA amyloid within the gastrointestinal tract. He had heavy proteinuria with a serum albumin of 15 g/L consistent with systemic AA amyloidosis. He had no symptoms to suggest an underlying chronic inflammatory condition but had CRP 130 mg/L and SAA 474 mg/L. In an attempt to identify the source of his inflammatory response, he underwent a contrast-enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…Although there is data demonstrating that serum amyloid A (SAA) protein is intensively expressed by malignant melanoma cells and could be a marker for predicting a high risk of tumor progression 18 , AA amyloidosis is an unusual complication of melanoma. A successful treatment of the underlying process can lead to the stabilization or improvement of renal function, reduction in protein excretion, and partial resolution of amyloid deposits 19 . Cancer cells are known to produce SAA protein 20 although AA amyloidosis is rarely associated with solid organ malignancies, metastatic disease and Hodgkin's lymphoma (< 7%) 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Although there is data demonstrating that serum amyloid A (SAA) protein is intensively expressed by malignant melanoma cells and could be a marker for predicting a high risk of tumor progression 18 , AA amyloidosis is an unusual complication of melanoma. A successful treatment of the underlying process can lead to the stabilization or improvement of renal function, reduction in protein excretion, and partial resolution of amyloid deposits 19 . Cancer cells are known to produce SAA protein 20 although AA amyloidosis is rarely associated with solid organ malignancies, metastatic disease and Hodgkin's lymphoma (< 7%) 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…AA amyloidosis is a paraneoplastic syndrome rarely associated with RCC (3–8% of cases) although several autopsies have suggested that RCC is the solid malignancy that most often causes AA amyloidosis, accounting for 25–42% of cases of solid tumors with secondary amyloidosis [ 1 , 6 , 8 , 16 ]. It is characterized by multisystem extracellular deposition of amyloid fibrils derived from cleavage fragments of the N -terminal portion of serum amyloid protein A [ 7 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first association between amyloidosis and renal cell carcinoma was described by Ask-Up-mark in 1940 [ 8 ]. We found in the literature 19 cases of AA amyloidosis secondary to RCC [ 6 ]. Amyloid deposits are documented in the kidney, gastrointestinal tract, retroperitoneum, liver, spleen, adrenal glands, conjunctiva, and upper respiratory tract mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some cases of AA amyloidosis caused by renal cell carcinoma have been reported [ 8 10 ]; in such cases, improvement in amyloidosis was achieved after removal of the carcinoma. However, levels of CRP, an acute-phase protein used as a tumor marker of renal cell carcinoma, did not change in our patient and proteinuria increased after nephrectomy.…”
Section: Discussionmentioning
confidence: 99%